(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The study focuses on the cultivation and yield of Itburun Na’matak (Rosa canina), a wild rose species, in the specific soil and climate conditions of the Surkhandarya region. This research investigates the optimal growing conditions, soil requirements, and the plant’s adaptability to the region. The results provide insights into potential agricultural and economic benefits, suggesting that Surkhandarya’s soil and climate are conducive to successful cultivation, with a promising yield for both local and commercial use.